2013
DOI: 10.1371/journal.pone.0070640
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Common Genetic Variants to Obesity and Obesity-Related Traits in Mexican Children and Adults

Abstract: BackgroundSeveral studies have identified multiple obesity-associated loci mainly in European populations. However, their contribution to obesity in other ethnicities such as Mexicans is largely unknown. The aim of this study was to examine 26 obesity-associated single-nucleotide polymorphisms (SNP) in a sample of Mexican mestizos.Methods9 SNPs in biological candidate genes showing replications (PPARG, ADRB3, ADRB2, LEPR, GNB3, UCP3, ADIPOQ, UCP2, and NR3C1), and 17 SNPs in or near genes associated with obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
70
4
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 46 publications
(57 reference statements)
12
70
4
6
Order By: Relevance
“…Waist/height ratio measures the abdominal fat in any gender or age and is a better metabolic risk predictor than BMI (Browning et al , 2010; Kodama et al , 2012). This result is in agreement with other studies in different populations (León-Mimila et al , 2013; Luczynski et al , 2012; Villalobos-Comparán et al , 2008; Xi et al , 2010). We also found that the A allele increases the risk of alterations in the lipid profile (cholesterol and HDL levels), as reported by other groups (Villalobos-Comparán et al , 2008; Mascarenhas-Melo et al , 2013).…”
Section: Discussionsupporting
confidence: 94%
“…Waist/height ratio measures the abdominal fat in any gender or age and is a better metabolic risk predictor than BMI (Browning et al , 2010; Kodama et al , 2012). This result is in agreement with other studies in different populations (León-Mimila et al , 2013; Luczynski et al , 2012; Villalobos-Comparán et al , 2008; Xi et al , 2010). We also found that the A allele increases the risk of alterations in the lipid profile (cholesterol and HDL levels), as reported by other groups (Villalobos-Comparán et al , 2008; Mascarenhas-Melo et al , 2013).…”
Section: Discussionsupporting
confidence: 94%
“…These polymorphisms have been shown to be associated with various metabolic traits such as obesity (24), body fat distribution (25), resting energy expenditure (26), type 2 diabetes (10) and insulin resistance (9,27) in various populations from different ethnic backgrounds (24). However, there were also studies that failed to show an association between these polymorphisms and metabolic traits (8,28,29). These inconsistencies could be attributed to the small sample size, incomplete coverage of the UCP2 gene variations or potential population-specific influences on metabolic traits (29).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in KCTD1 in humans are responsible for scalp-ear-nipple (SEN) syndrome (Marneros et al, 2013), but it is not known whether inhibition of AP-2 or Wnt signaling plays a role in the etiology of this disease. KCTD15 is not been reported as the cause of a disease, but numerous studies show an association between this gene and obesity (Gutierrez-Aguilar et al, 2012; Leon-Mimila et al, 2013; Mei et al, 2012; Willer et al, 2009; Williams et al, 2012). It is known that AP-2α regulates the activity of C/EBPα during adipogenesis (Jiang et al, 1998), and AP-2β affects other steps of adipogenesis and insulin resistance (Ikeda et al, 2006; Meng et al, 2010; Tao et al, 2006; Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%